MODERN METHODS IN FOREIGN LANGUAGE TEACHING METHODOLOGY - Boqiyeva Marjona Shuhratovna (Лучшие интеллектуальные исследования, 2023)
Annotation: This article is about the methodology of foreign language teaching as a science history of development, modern method used in foreign language teaching methodology types and their use are discussed.